Dynamic electrochemical impedance study of fluoride conversion coating on AZ31 magnesium alloy to improve bio‐adaptability for orthopedic application. Issue 4 (8th January 2019) - Saranya, Kannan; Kalaiyarasan, Madhu; Chatterjee, Suvro; Rajendran, Nallaiyan
Abstract : In the present work, fluoride conversion coating was formed on AZ31 magnesium alloy at 40 °C and the conversion time was optimized. A smooth surface with pores were formed which was observed from SEM. The crystalline MgO and MgF2 formed on the surface were confirmed by EDAX and X‐ray diffraction (XRD). The investigation on corrosion behavior of the coating was performed using potentiodynamic polarization, potentiostatic polarization and dynamic electrochemical impedance studies (DEIS). The coating stability was studied at various potentials ranging from −1.78 to −1.09 V which depicts that the coating was stable for wide range of potentials as compared to the substrate. The in vitro biomineralization of the coating was analyzed by immersing in Earle's solution for 7 days and the formation of nanospherical carbonated apatite with fluorine and magnesium was revealed by SEM/EDAX and ATR‐IR spectroscopy. The osteointegration and proliferation of MG63 and MSC cells on the coating were examined using MTT assay. Abstract : Fluoride conversion coating was formed on AZ31 magnesium alloy at 40 °C and the conversion time was optimized. A smooth surface with pores were formed which was observed from SEM. The coating stability was studied at various potentials ranging from −1.78 to −1.09 V which depicts that the coating was stable for a wide range of potentials as compared to the substrate.